From data collection to design principles: A study of smartwatch faces for enhanced information visualization - Miaomiao Dong; Ze Bian; Yuan Zhu (PLoS ONE, 2025)
With the surge in smartwatch popularity, presenting diverse data on a compact screen poses significant challenges. Previous research has primarily focused on the visual design of smartwatch faces, with limited exploration into how information interacts with users. Moreover, these studies have inadequately addressed interaction and practicality in information visualization. Our work analyzed 518 Huawei and 435 Facer smartwatch faces, synthesizing existing design elements and integrating insights from prior literature to propose a structured design framework that encompasses five key dimensions: content, composition, style, interaction, and practicality. This comprehensive framework not only addresses the visual and functional aspects but also emphasizes the importance of user engagement and individual preferences. By providing detailed guidelines, our framework aims to enhance the interaction, usability, and overall user experience of smartwatch face information visualization, paving the way for more effective and user-centric designs.